Neurophysiological mechanisms of cortical plasticity impairments in schizophrenia and modulation by the NMDA receptor agonist D-serine - Kantrowitz, Joshua T.; Epstein, Michael L.; Beggel, Odeta; Rohrig, Stephanie; Lehrfeld, Jonathan M.; Revheim, Nadine; Lehrfeld, Nayla P.; Reep, Jacob; Parker, Emily; Silipo, Gail; Ahissar, Merav; Javitt, Daniel C. (Brain (London, England : 1878), 2016)
Schizophrenia is associated with deficits in cortical plasticity that affect sensory brain regions and lead to impaired cognitive performance. Here we examined underlying neural mechanisms of auditory plasticity deficits using combined behavioural and neurophysiological assessment, along with neuropharmacological manipulation targeted at the N-methyl-D-aspartate type glutamate receptor (NMDAR). Cortical plasticity was assessed in a cohort of 40 schizophrenia/schizoaffective patients relative to 42 healthy control subjects using a fixed reference tone auditory plasticity task. In a second cohort (n = 21 schizophrenia/schizoaffective patients, n = 13 healthy controls), event-related potential and event-related time-frequency measures of auditory dysfunction were assessed during administration of the NMDAR agonist d-serine. Mismatch negativity was used as a functional read-out of auditory-level function. Clinical trials registration numbers were NCT01474395/NCT02156908 Schizophrenia/schizoaffective patients showed significantly reduced auditory plasticity versus healthy controls (P = 0.001) that correlated with measures of cognitive, occupational and social dysfunction. In event-related potential/time-frequency analyses, patients showed highly significant reductions in sensory N1 that reflected underlying impairments in θ responses (P < 0.001), along with reduced θ and β-power modulation during retention and motor-preparation intervals. Repeated administration of d-serine led to intercorrelated improvements in (i) auditory plasticity (P < 0.001); (ii) θ-frequency response (P < 0.05); and (iii) mismatch negativity generation to trained versus untrained tones (P = 0.02). Schizophrenia/schizoaffective patients show highly significant deficits in auditory plasticity that contribute to cognitive, occupational and social dysfunction. d-serine studies suggest first that NMDAR dysfunction may contribute to underlying cortical plasticity deficits and, second, that repeated NMDAR agonist administration may enhance cortical plasticity in schizophrenia.